Efficacy and Adverse Reactions of Arthroscopic Half-Moon Plate Invasive Surgery in Patients with Acute Knee Pain (AKP): Systematic Review and Meta-Analysis - Luping Sun; Zhidan Huang (Applied Bionics and Biomechanics)
Objective. To evaluate the efficacy and adverse reactions of arthroscopic half-moon plate invasive surgery (DEB) in patients with knee pain (AKP) using meta-analysis techniques. Methods. The computer retrieves from the English databases PubMed, EMBASE, Cochrane Library, and Web of Science and the Chinese databases China Knowledge Network, Wanfang Database, VIP Database, and China Biomedical Literature Database to collect information about DEB therapeutic AKP randomized controlled trial. Develop criteria for documentation inclusion and exclusion, evaluate the quality and bias risk of literature, and compare differences in efficacy and adverse responses before and after DEB treatment and other conservative treatments. Results. A total of 14 randomized controlled trials and 1464 AKP patients were included in the study, with follow-up duration of 1-12 months. The total knee scores for DEB at 1, 3, 6, and 12 months after treatment were significantly better than baseline levels (1 month: WMD=34.56, P=0.02; 3 months: WMD=27.73, P=0.0001; 6 months: SMD=2.38, P=0.0001; 12 months: SMD=1.69, P=0.001). At 6 months of follow-up, DEB improved knee function better than HA (SMD=0.47, P=0.003), and during follow-up for 12 months, DEB relieved knee pain (SMD=0.55, P=0.0007) and improved knee function (SMD=0.88, P=0.0001) which is significantly better than HA. DEB was less effective at improving knee function in 1, 3, and 12 months than DEB joint HA injections (1 month P=004; 3 months P=0.01; 12 months P=0.03). At 6 and 12 months of follow-up, DEB was better at pain relief and improved function than ozone (P>0.05). DEB and glucocorticosteroids have similar effects in pain relief and improved function at various follow-up times. In terms of adverse reactions, DEB does not increase the risk of adverse events compared to HA (OR=0.96, P=0.85). Conclusion. Compared to HA and ozone, DEB is a more effective treatment for AKP joints, while DEB is combined with HA. The clinical efficacy of injection therapy AKP is better than that of DEB alone.